Incentive Funding for Innovative Activities - Valerii P. Shestak (Финансы: теория и практика)
Topic. The topic of this research is the stimulation of innovative activity of industrial enterprises as one of the basic conditions of industrial growth of the Russian economy. It is especially important in the conditions of sanction problems.Purpose. The purpose of the study is to determine the optimal funding mechanism for innovative projects in industry, primarily aimed at stimulation of innovation activity against the systemic failure indicators of Russia in various international rankings.Methodology. The purpose of the study is achieved by the fullest understanding of key aspects of the innovation process: methodology of the research includes philosophical and political-economic methods. The essence of the philosophy of innovation is represented as a process (innovation) chain of turning ideas into socialized and competitive product on the market. Such chains provide the update of all spheres of life at every stage of development of society, lead to the accumulation of cultural heritage and the transition to a higher level of existence. In turn, the essence of the political economy of innovation is that the innovation chain is implemented in the society in which there are any questions as concerns the productive forces and production relations. Thus, ideological consolidation of society plays a major role. From proper state regulation of the conditions for innovation and its stimulation depends not only the success of enterprises, but also the socio-economic development of the country — welfare of citizens.Results. To improve the efficiency of financial-economic and social mechanisms of stimulation of innovative activity it is proposed implementation of project financing mechanism for innovation chain as a whole, considering it as a single project “financing in a shell nut.”Conclusions. Using the format of public-private partnerships and converged “triple helix” mechanism of project financing it is possible to stimulate innovative activity in industrial enterprises by kind of “coercion to innovations.”